HopAZ1, a type III effector of Pseudomonas amygdali pv. tabaci, induces a hypersensitive response in tobacco wildfire‐resistant Nicotiana tabacum 'N509'. (1st March 2022) - Kashihara, Sachi; Nishimura, Takafumi; Noutoshi, Yoshiteru; Yamamoto, Mikihiro; Toyoda, Kazuhiro; Ichinose, Yuki; Matsui, Hidenori
Abstract: Pseudomonas amygdali pv. tabaci (formerly Pseudomonas syringae pv. tabaci ; Pta) is a gram‐negative bacterium that causes bacterial wildfire disease in Nicotiana tabacum . The pathogen establishes infections by using a type III secretion system to inject type III effector proteins (T3Es) into cells, thereby interfering with the host__s immune system. To counteract the effectors, plants have evolved disease‐resistance genes and mechanisms to induce strong resistance on effector recognition. By screening a series of Pta T3E‐deficient mutants, we have identified HopAZ1 as the T3E that induces disease resistance in N. tabacum 'N509'. Inoculation with the Pta ∆ hopAZ1 mutant did not induce resistance to Pta in N509. We also found that the Pta ∆ hopAZ1 mutant did not induce a hypersensitive response and promoted severe disease symptoms in N509. Furthermore, a C‐terminal truncated HopAZ1 abolished HopAZ1‐dependent cell death in N509. These results indicate that HopAZ1 is the avirulence factor that induces resistance to Pta by N509. Abstract : Nicotiana tabacum 'N509' recognizes the Pseudomonas amygdali pv. tabaci type III effector HopAZ1 as an avirulence factor.